Influences on intentions for obstetric practice among family physicians and residents in Canada: an explorative qualitative inquiry - Marshall, Emily G.; Horrey, Kathleen; Moritz, Lauren R.; Buote, Richard; Grudniewicz, Agnes; Goldsmith, Laurie J.; Randall, Ellen; Jones, Lori; Lavergne, M Ruth (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background Many family medicine residency graduates indicate a desire to provide obstetric care, but a low proportion of family physicians (FPs) provide obstetric care within their practice. This suggests personal preference alone may not account for the low proportion of FPs who ultimately provide full obstetric care. If decisionmakers plan to augment the number of FPs providing obstetric care, barriers to the provision of such care must first be identified. Within this paper, we explore the perspectives of both family practice residents and early-career FPs on the factors that shaped their decision to provide obstetric care. Methods In this qualitative study, we analyzed a subset of interview data from three Canadian provinces: British Columbia, Ontario, and Nova Scotia (n = 18 family practice residents; n = 39 early-career FPs). We used thematic analysis to analyze data relevant to obstetric care practice, applying the socio-ecological model and comparing themes across participant types, gender, and province. Results Participants described influences affecting their decision about providing obstetric care. Key influencing factors aligned with the levels of the socio-ecological model of public policy (i.e., liability), community (i.e., community needs), organizational (e.g., obstetric care trade-offs, working in teams, sufficient exposure in training), interpersonal practice preferences (i.e., impact on family life, negative interactions with other healthcare professionals), and individual factors (i.e., defining comprehensive care as “everything but obstetrics”). Many participants were interested in providing obstetric care within their practice but did not provide such care. Participants’ decision-making around providing or not providing obstetric care included considerations of personal preferences and outside influences. Conclusions Individual-level factors alone do not account for the decrease in the type and amount of obstetric care offered by FPs. Instead, FPs’ choice to provide or not provide obstetric care is influenced by factors at higher levels of the socio-ecological model. Policymakers who want to encourage obstetric practice by FPs should implement interventions at the public policy, community, organizational, interpersonal, and individual levels.